2006
DOI: 10.1038/oby.2006.75
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone Treatment Results in Obesity and Altered Lipid Metabolism in Orchidectomized Mice

Abstract: Research Methods and Procedures: Orchidectomized mice were treated with the non-aromatizable androgen 5␣-dihydrotestosterone (DHT), 17␤-estradiol, or vehicle. VO 2 , VCO 2 , resting metabolic rate, locomotor activity, and food consumption were measured. Furthermore, changes in hepatic gene expression were analyzed. Results: DHT treatment resulted in obesity, associated with reduced energy expenditure and fat oxidation. In contrast, DHT did not affect food consumption or locomotor activity. Furthermore, DHT tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 60 publications
9
72
0
Order By: Relevance
“…Importantly, however, Lin et al did not measure testosterone levels in high-fat diet-fed animals and thus could not determine whether increased hepatic steatosis was due to AR function or an obesity-related testosterone decline. By contrast, hepatic Scd1 mRNA expression was increased following DHT treatment in orchidectomised obese mice compared with placebo-treated controls (Movérare-Skrtic et al 2006). Significantly elevated Scd1 expression also remained when compared to sham-operated controls, suggesting possible pharmacological effects of DHT administration.…”
Section: Livermentioning
confidence: 65%
See 1 more Smart Citation
“…Importantly, however, Lin et al did not measure testosterone levels in high-fat diet-fed animals and thus could not determine whether increased hepatic steatosis was due to AR function or an obesity-related testosterone decline. By contrast, hepatic Scd1 mRNA expression was increased following DHT treatment in orchidectomised obese mice compared with placebo-treated controls (Movérare-Skrtic et al 2006). Significantly elevated Scd1 expression also remained when compared to sham-operated controls, suggesting possible pharmacological effects of DHT administration.…”
Section: Livermentioning
confidence: 65%
“…At the same time, microsomal triglyceride transfer protein was decreased by DHT, thus reducing apolipoprotein B-mediated very LDL (VLDL) secretion. Cholesterol 7a-hydroxylase, a key enzyme in bile acid formation and therefore removal of cholesterol from the body, was decreased following DHT administration in this study, leading to hepatic lipid accumulation due to increased cholesterol uptake but decreased removal (Movérare-Skrtic et al 2006). Contrariwise, AR-independent effects on hepatic steatosis and lipid metabolism have been demonstrated in the Tfm mouse (Kelly et al 2012).…”
Section: Livermentioning
confidence: 71%
“…Indeed, administration of gens such as testosterone in older me and abdominal fat and increases whereas in vivo and in vitro studies s play a significant role in altering fa distribution [50][51][52][53]. ARs are found in more being present in visceral compa depots [54].…”
Section: Neuroendocrine Control Of Bone and Fatmentioning
confidence: 99%
“…The 3.0 mg/kg/d dosage of DHT was chosen because it was shown that this dosage can restore the weight of the ventral prostate (VP) in ORX rats (control: 0.062 ± 0.13 g/VP; ORX: 0.02 ± 0.01 g/VP; DHT: 0.070 ± 0.32 g/VP). The 1.0 mg/kg/d dosage of E2 was chosen because this dosage was shown to prevent ORX-induced trabecular bone loss (Moverate-Skrtic et al, 25 ). Subcutaneous injections were given to all animals at the same time (16:00 h).…”
mentioning
confidence: 99%